Teaching and learning mathematics and science in English in primary schools in the state of Johor, Malaysia - Selamat, Asri; Esa, Ahmad; Saad, Shamsaadal Sholeh; Atim, Asliaty (JABATAN PERKEMBANGAN KURIKULUM KEMENTERIAN PENDIDIKAN NEGARA BRUNEI DARUSSALAM, 2011)
This article attempts to highlight the opinions of the public on the effectiveness of the use of English in teaching and learning Mathematics and Science (PPSMI) in primary schools in Johor. After nearly six years of its implementation, some people found out that the students have not demonstrated a good command of the language and the acquisition of knowledge of Mathematics and Science is seen to be declining. The teachers also do not seem to adapt well in the implementation. A group of respondents from among the headmasters and headmistress have given their views through a questionnaire and structured interview that showed the government's intention to strengthen the English language in teaching and learning Mathematics and Science did not show an impressive result. Thus, the study suggests that the government can try to give an option of using both languages in the implementation of this policy.